A representatividade sindical e a questão da prevalência do negociado sobre o legislado - Souza, Fernanda Donata de (2021)
The Labor Reform made through federal law n. 13.467/17 altered several articles of the Consolidation of Labor Laws (CLT) and established, among several points, the prevalence of the negotiated over the law, in the hypotheses established by the article 611A of the CLT. Despite the prediction that the negotiated should prevail over the legislature, the Labor Reform has substantially weakened one of the most important parts in this negotiation: the syndicate.In fact, syndicates are currently facing a political process of weakening of their proceeding, their competencies and their financial base through several infraconstitutional changes, even though in recent years the National Congress has not approved any constitutional amendment reducing their competences, guarantees and rights. Among these changes are the creation of the figure of the hypersufficient, who can negotiate directly with the employer without the intervention of the syndicate, the determination that the collective agreement between syndicate and one or more enterprises (restrict) must always prevail over the conditions established in a collective labor agreement between two or more syndicates (wider), even if this wider agreement is more favorable to the employee, the revocation of the prevision that guaranteed the prevalence of the wider collective agreement over the restricted collective agreement in the hypothesis of being more favorable to the employee, and the extinction of the compulsory syndicate contribution.It seems evident that the objective of the latest legislative changes was not to protect or benefit employees, but to privilegie the capital. Such an aspect can be seen in the Labor Reform forecast that lactating and pregnant women could work in an unhealthy environment, a hypothesis that was only later removed by the Supreme Court.It is essential to analyze carefully the importance of unions for labor relations, as well as their historical evolution and their main duties. It is also essential to analyze the questions raised against the latest legislative changes that have weakened the unions, whether those filed with the Supreme Court or those made with the International Labor Organization. Only with a properly structured and strong union we can imagine an effective and fair collective bargaining between employees and employers, thus ensuring greater balance between the capital and the workforce involved